Orthogonal Genetic Algorithm for Planar Thinned Array Designs - Li Zhang; Yong-Chang Jiao; Bo Chen; Hong Li (International Journal of Antennas and Propagation)
An orthogonal genetic algorithm (OGA) is applied to optimize the planar thinned array with a minimum peak sidelobe level. The method is a genetic algorithm based on orthogonal design. A crossover operator formed by the orthogonal array and the factor analysis is employed to enhance the genetic algorithm for optimization. In order to evaluate the performance of the OGA, 20×10-element planar thinned arrays have been designed to minimize peak sidelobe level. The optimization results by the OGA are better than the previously published results.